GIANT PYOGENIC GRANULOMA - A CASE REPORT - Hassan Iffat; Mashkoor Wani; Hassan Zareena (Our Dermatology Online, 2011)
Pyogenic granuloma (PG) is a relatively common benign vascular lesion of the skin and mucosa. The exact cause is not known but multiple factors have been implicated in the etiology of pyogenic granuloma. The PG typically evolves rapidly over a period of few weeks. It can mimic a number of malignant tumors making the histopathological examination of lesion necessary. Very large size PGs are very rare. We report this rare case of a giant pyogenic granuloma in a ninety three year old, otherwise healthy, female patient.